AB0940 The Prevalence of Achalasia among Patients with Autoimmune Diseases. (10th June 2014) - Katada, Y.; Harada, Y.; Yura, A.; Yoshimura, M.; Katayama, M.; Teshigawara, S.; Tanaka, E.K.; Watanabe, A.; Oshima, S.; Tsuji, S.; Saeki, Y.; Murata, J.; et al.
Abstract : Background: Esophageal achalasia is a rare disease characterized by degeneration of Auerbach's plexus. Although its presumed etiologies include autoimmune process, its precise mechanisms remain uncertain. Recently, it has reported that patients with achalasia are more likely to have autoimmune diseases. Objectives: To elucidate the significance of achalasia in patients with autoimmune diseases Methods: The computerized medical records system of our medical center were screened for patients with systemic lupus erythematosus (SLE), systemic sclerosis (SSc), polymyositis (PM)/dermatomyositis (DM), and achalasia for recent 30 years (between 1982 and 2012). Then the details of picked up patients were investigated. Results: Twelve patients with achalasia were identified. Among them, 1 patient was also with SLE and 2 patients with SSc (table). All of them experienced nocturnal coughing with regurgitation of ingested food without gastric acid and suffered from aspiration pneumonia. Interestingly, all these 3 patients had autoantibodies relating to SSc (scl-70 or centromere), although patient 1 had no sign indicating SSc. The prevalence of such autoimmune diseases in achalasia patients was 25% (3/12). Inversely, the prevalence of achalasia in SLE patients was estimated at 0.19% (1/539), while that in SSc patients 0.67% (2/297). These patients are 19 times and 67 times more likely to suffer from achalasia compared with general population (1/10000), respectively. None of the 98 patients with PM and of 55 patients with DM had achalasia. The onset of achalasia could be before, at the same time as, or after that of autoimmune diseases. Conclusions: The prevalence of achalasia among patients with autoimmune diseases (especially SSc) is much higher than that in general population. When patients with autoimmune diseases present recurrent regurgitation of food without gastric acid, esophageal achalasia must be ruled out, considering it might be underdiagnosed. Patients with SSc can exhibit similar symptoms, having reflux esophagitis.However, their regurgitations are usually with gastric acid. This is an important point for differential diagnosis. Further study is required to reveal its nature and clinical significance. References: Booy JD. Et al. Dis Esophagus. 2012;25:209-13. Katada N. et al. Ann Thorac Cardiovasc Surg 2012; 18: 420–428. Gockel I. et al. Dtsch Arztebl Int. 2012;109:209-14. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4910